Análises química, antioxidante e e citotoxicidade em linhagens tumorais de germoplasma de Eplingiella fruticosa - Pinto, Jéssika Andreza Oliveira (2022)
Eplingiella fruticosa is an aromatic plant of the Lamiaceae family known as “alecrim-devaqueiro”. Its popular use has aroused the interest of the scientific community regarding the possible pharmacological properties involved, and the anti-hyperalgesic, antinociceptive, antiinflammatory, vasodilatory and anti-neurodegenerative effects have already been attributed to its essential oil and extracts. The first article investigated the variations in the chemical profiles and biological activities (antioxidant and cytotoxicity) of Eplingiella fruticosa from the State of Sergipe. The essential oils of six populations were extracted by hydrodistillation and analyzed by Gas Chromatography coupled to a Mass Spectrometer and a Flame Ionization Detector (GC/EM-DIC). The antioxidant activity of the essential oils was tested by different assays (DPPH, ABTS, β-carotene and FRAP) and the cytotoxic activity was determined by the SRB assay. The compounds found in greater amounts were: α-pinene, β-pinene, 1,8-cineole, camphor, borneol, δ-elemene, α-cubebene, α-ylangeno, (E)-caryophyllene, germacrene D, bicyclogermacrene, trans -calamenene, spathulenol, caryophyllene oxide and viridiflorol. These compounds defined the formation of two groups. The first group consisted of the populations of São Cristóvão, Itaporanga, Japaratuba and Malhada dos Bois and was characterized by the presence of camphor monoterpene (8.39-11.27%) as the highest content compound in relation to the other municipalities. The second group consisted of the populations of Moita Bonita and Pirambu and was characterized by the majority presence of bicyclogermacrene sesquiterpene (7.45% and 10.98%). The plants showed weak effects in terms of antioxidant activity, but the essential oil showed significant toxicity for the A549 strains (51.00% cell viability) in the population of Japaratuba and B16F10 (64.94.6% of cell viability) in Malhada of the Oxen. The second article analyzed the chemical profile, antioxidant activity and cytotoxicity of aqueous and ethanolic extracts from populations of E. fruticosa. The extracts were analyzed by High Performance Liquid Chromatography (HPLC). Antioxidant activity and cytotoxic activity were tested in the same way as in the first article. The flavonoid quercitrin was identified in the ethanol extract. The aqueous extracts showed higher antioxidant activity in relation to the other extracts. The DPPH and ABTS radicals range from 84.89- 75.62% and 85.21-64.04%, respectively, in the aqueous extracts. The ethanol extracts from the populations of Japaratuba, São Cristóvão and Itaporanga d'Ajuda showed the highest inhibitory activities with 90.63%, 90.53% and 88.47% for the C6 strain and the hydrodistilled ethanol extract from the Japaratuba population showed high growth inhibition at A549 (87.17% cell viability) and C6 (72.83% cell viability). The observations from these studies show that E. fruticosa can be a significant source of medicinally important natural compounds.